Re-Thinking US Foreign Policy in Southeast Asia: Is it Containment Against China or Against Terrorism? - Omi Ongge (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : The dynamic of the United States foreign policy toward Southeast Asia is very much affected and influenced by the rise of China and the terrorism thread in 21st century. In the era of first Bush Administration, US foreign policy was focusing on the issue of terrorism after the 9/11 tragedy. In this issue, US was engaging Indonesia and Philippines in terms of military cooperation and security. Meanwhile, in the second Bush Administration the main focus of US foreign policy was flipped into the containment against China due to the influence of China into Southeast Asia in terms of economics (free trade agreement). In the era of Obama first administration, US eventually prioritized the SEA region both bilaterally and multilaterally, which is different from the Bush administration. However, the scope of the policy remains, the same to the previous one, on the containment against China and terrorism. U.S under Obama remains emphasis on the three main elements of the containment policy; economic, alliance/partnership and diplomacy with more concentration than the Bush’s. It can be concluded that this enhanced US posture in Southeast Asia is Washington’s recognition that ASEAN is the core of both regional security and economic activities and that the US must play a major role in regional affairs as well as continuing to strengthen bilateral ties.Keywords: US Foreign Policy, China, Southeast Asia, ASEAN, Terrorism, and Containment policy,